Inhibition of glucocorticoid-induced REDD1 expression by rapamycin in breast cancer cells - D. D. Grigorieva; E. M. Zhidkova; E. S. Lylova; D. V. Demina; K. I. Kirsanov; G. A. Belitsky; M. G. Yakubovskaya; E. A. Lesovaya (Успехи молекулярной онкологии)
Introduction. Glucocorticoids are often used in combination therapy for breast cancer as an adjuvant to increase therapeutic effects of the main cytotoxic drug and to reduce side effects of chemotherapy. However, glucocorticoids can cause serious complications and trigger tumor progression. In the last decade, it was found that side effects from glucocorticoids are mediated by an increase in REDD1 gene expression. Using this knowledge, we have developed a new chemotherapeutic strategy for blood cancers aimed at reducing adverse events from glucocorticoids. Successful experiments with a combination of glucocorticoids and REDD1 expression inhibitors on the models of blood tumors allowed us to use this regimen for the treatment of certain subtypes of breast cancer.Objective: to optimize the algorithm of breast cancer cell treatment with a combination of glucocorticoids and REDD1 expression inhibitors on the example of rapamycin.Materials and methods. We used the MCF-7 and MDA-MB-231 breast cancer cell lines. The antiproliferative activity was estimated by direct cell count; REDD1 expression was measured using western blotting and quantitative polymerase chain reaction.Results. We found that rapamycin can inhibit both baseline and glucocorticoids induced REDD1 expression in the cells of luminal and triple negative breast cancer. The drug demonstrated lower ability to inhibit the viability of breast cancer cells than that of leukemia and lymphoma cells.Conclusion. Inhibited proliferation of breast cancer cells after their incubation with rapamycin and dexamethasone, as well as the ability of rapamycin to reduce basal and glucocorticoid-induced REDD1 expression in breast cancer cells suggest the importance of studies analyzing the impact of combinations that include glucocorticoids and REDD1 expression inhibitors from the class of PI3K/Akt/mTOR signaling pathway modulators (phosphoinositide-3-kinase/α-serine-threonine kinase/mammalian rapamycin target) on breast cancer cells.